La problématique de la révision constitutionnelle en RDC : Analyse des enjeux du cycle électoral 2013-2016 - Salumu, Fiston WANDJA; FUMBA LITEMBU mwenga LIPANDA Sylvain,; MOSONGO BOFANDO Charles,; MASAMPU NTUMWA Trésor, (IJRDO - Journal of Social Science and Humanities Research, 2020)
As part of this research, we are therefore interested in carrying out a scientific analysis of the challenges of the 2013-2016 electoral cycle on the issue of constitutional revision in the Democratic Republic of Congo, dates on which, we had to note that some political speeches announce the attempt at constitutional revision even in these intangible provisions. Around the world in general, and in the Democratic Republic of Congo in particular, constitutions have often been subject to several types of modifications, having taken mutatis mutandis different types of names depending on the circumstances. Sometimes we talk about suspension or repeal, sometimes change, sometimes revision. We started from an irrefutable constant, observable with the naked eye that, the constitutional revision on the one hand, is a trick which favors the development of a nation by the alternation in power. On the other hand, is a support for the conversationalist culture of power and hegemonic and insatiable ambitions. It is also necessary to note the practice of deconstitutionalization-reconstitutionnalisation which, without any doubt, generates imperfections, frauds and constitutional disputes.